Relationship of Mother's Behavior with Basic Immunization at Public Health Center Pekanbaru City - Aspiati; Ristika Julianty Singarimbun (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Immunization is a way to actively increase a person's immunity against an antigen, so when he is later exposed to a similar antigen, disease does not occur. The purpose of immunization is prevent the occurrence of certain diseases in group of people or even eliminate certain diseases from world, such as measles immunization. Mother's behavior about immunization form a positive attitude towards immunization activities. With the good knowledge, attitudes and actions that mother has, the awareness to immunize the baby will increase. The knowledge, attitudes and actions possessed by mother will raise the mother's confidence in health of baby and affect status of immunization in Indonesia. The research conducted is correlational quantitative data with a cross sectional design. The research was conducted at Pekanbaru City Health Center in August - December 2021. The study population was mothers who visited Pekanbaru City Health Center to immunize their babies, namely as many as 60 people. Sampling was done total sampling. The data collected in this research is of primary data which is collected directly from the respondents using a questionnaire. The results showed that mother's behavior regarding basic immunization was good for 20 people 33.3%, sufficient behavior for 13 people 21.7%, and poor behavior for 27 people 45.0%. From the results of study it is hoped that the Public Health Center can provide information about immunization to mothers who have babies and visit the Pekanbaru City Health Center to be more active and many mothers are enthusiastic about bringing their children to Integrated Healthcare Center every month.